Access to Multicultural/Multiethnic Grey Literature: A Networked Approach Asian American Resources - Li, Marjorie H. (GreyNet International, Grey Literature Network Service, 1998)
Multicultural/multiethnic GL is a concept first introduced and defined at the GL'95. Multi-cultural/ multiethnic GL, although considered primary resources, have been fragmented and scattered or buried within other reports and documents making them difficult to identify and access. If these materials are to be of any real value, they must be located, organized, and made accessible to the communities they represent as well as to the general public. GL`95 presentations focused on the opportunities presented by new and emerging technologies for the management and redistribution of GL. Moreover, the Web is an emerging vehicle in which to expand the range of materials available to the public and to better coordinate their accessibility. Our goal is to present an enhanced networked-based product which will provide effective access to multicultural/ multiethnic GL. The Asian-American communities serve as our model.